2013
DOI: 10.1111/rode.12018
|View full text |Cite
|
Sign up to set email alerts
|

Disfavored Nations: Anti‐Dumping at the WTO

Abstract: The proliferation of Anti-Dumping actions may be explained by the Most Favored Nation rule of safeguards, the advantages of unilateral retaliatory measures as an alternative to formal dispute resolution, and the exercising of discipline in a risk-sharing agreement. Use of unilateralism is attractive to developing members that are constrained by legal capacity. The expression of the Anti-Dumping Agreement appears to be a hybrid of rules and standards. However, a lack of interpretive guidance from the WTO and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Of course, there may be other ways that countries (and/or the targeted firms) can respond (health and safety regulatory restrictions, escape clause/safeguard cases, or simply raising applied tariffs if below bound levels), and we do not claim to be capturing all of these in our work. 4 2 Hartigan and Vandenbussche (2013), in a theoretical and legal analysis, discuss how retaliatory AD may substitute for and -in some cases-be preferable to DSU litigation, especially for developing countries. 3 At the time we started this research, we observed anti-dumping filings through 2014 and so limit our sample to the period from 1995 to 2011 to allow up to 3 years for a country to file a retaliatory dispute at the WTO.…”
Section: Theoretical Motivationmentioning
confidence: 99%
See 2 more Smart Citations
“…Of course, there may be other ways that countries (and/or the targeted firms) can respond (health and safety regulatory restrictions, escape clause/safeguard cases, or simply raising applied tariffs if below bound levels), and we do not claim to be capturing all of these in our work. 4 2 Hartigan and Vandenbussche (2013), in a theoretical and legal analysis, discuss how retaliatory AD may substitute for and -in some cases-be preferable to DSU litigation, especially for developing countries. 3 At the time we started this research, we observed anti-dumping filings through 2014 and so limit our sample to the period from 1995 to 2011 to allow up to 3 years for a country to file a retaliatory dispute at the WTO.…”
Section: Theoretical Motivationmentioning
confidence: 99%
“… Hartigan and Vandenbussche (), in a theoretical and legal analysis, discuss how retaliatory AD may substitute for and—in some cases—be preferable to DSU litigation, especially for developing countries. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…25 See Hartigan and Vandenbussche (2013 investigations simultaneously against China in 2006, generating legal controversy at the U.S. Court of International Trade and the U.S. Court of Appeals for the Federal Circuit. Ramanujian and Sampath (2015) critique panel and AB reports over this pairing of measures.…”
Section: Is This An Ad Case?mentioning
confidence: 99%
“…12 The Anti-dumping Agreement (ADA) of the WTO may be considered an alternative form of SG. Hartigan and Vandenbussche (2013) have considered the ADA from the perspective of rules and standards. 13 I recognise that disputes have been increasing in frequency, particularly with regard to China.…”
mentioning
confidence: 99%